IMPLENTATION MODEL, VIEW AND COTROLLER (MVC) METHOD ON ONLINE LIBRARY - Heru Purwanto; Tri Hartanti; Noer Hikmah (Journal of Information System, Informatics and Computing, 2023)
The development of computer technology has made services more effective and efficient. The library management process at SDN Bekasi Jaya VII has not been computerized so that library management has not been maximized. The aim of this research is to implement an online library information system. By utilizing the internet, it is hoped that library management will be better. The Model, View and Controller (MVC) architectural pattern is an option in facilitating system design and creating applications. Through the creation of online library services, it is hoped that it will make it easy for members to find out book information, borrow and return books and assist librarians in managing books, making reports faster. Testing the t-test with t hit statistical test (n <30), α = 0.05 was carried out to measure the effectiveness of the influence of online library applications, where the result is t count = 2.52 > t 0.025; 28 = 2.048 indicating that there is an influence to be able to improve library services through availability of library information